Monitoring Pregnancy Status in Captive Asian Elephants (Elephas maximus) of Sauraha, Nepal Based on Blood Progesterone Profile - Nepal, Grihamani; Gautam, Gokarna; Gairhe, Kamal Prasad; Sadaula, Amir; Pathak, Chet Raj; Devkota, Bhuminand (Journal of Agriculture and Forestry University, 2025)
Progesterone is the major reproductive hormone in female elephants to maintain pregnancy and is produced by the corpus luteum (CL) and placenta. This study routinely monitored the pregnancy status of captive Asian elephants (Elephas maximus) of Sauraha, Nepal, based on individual blood progesterone profiles. The five captive Asian elephants were selected from the Elephant Breeding Center (EBC) and the National Trust for Nature Conservation (NTNC). A purposive sampling technique was adopted to collect blood samples at an interval of a month for 16 months from the ear vein using a vacutainer set with 18-gauge needles. Blood progesterone concentrations were measured from blood serum samples using an enzyme linked immunosorbent assay (ELISA). The serum progesterone concentration in non-pregnant elephants ranged from 57.01 pg/ml to 123.10 pg/ml (an average: 93.27±6.98 pg/ml) and in pregnant elephants (89.94-340.90) pg/ml, but at mid-gestation, its minimum concentration was 250 pg/ml. In this study, in pregnant elephants, the trend of serum progesterone concentration peaked at mid-gestation and became lowest at late gestation was observed. These findings in disparities in the concentration of serum progesterone levels between non-pregnant and pregnant elephants, with the help of ELISA, could be an avenue in the prediction of pregnancy status in Asian elephants.